COMPUTERS IN SPECIFIC AREAS OF UNIVERSITARY TEACHING - Santisteban-Requena, Carmen (Anales de Psicología / Annals of Psychology)
The main goal of this study is the evaluation and control of learning in computerized instructional environments. Considering the components of learning and performance models, tree simulation models and experiences on University student of Psychometry have been carried out to investigate the better instructional design to increase their knowledge of the basic concepts, to enhance their problem-solving skills and their sense of self-confidence using formulas and, additionally, to increase their comfort with computers as an educational tool.